Low Noise, High Gain RF Front End Receiver at 5.8GHz for WiMAX Application - Othman, Abdul Rani; Hamidon, Abdul Hamid; Abdul Wasli, C; Mustaffa, M. F; Ting, J. T. H; Ibrahim, A. B (UTeM, 2010)
This paper presents the design of a high gain, low noise direct conversion Radio frequency(RF) front-end receiver system. The Front end receiver is designed to operate at 5.8 GHz in compliant with IEEE 802.16 WiMAX standard. The system consists of a low noise amplifier (LNA), a radio frequency amplifier (RFA), a power divider and two band pass filters. The design process involved the use of software such as ADS 2000A, Ansoft Designer and MathCad. FET FHX76 LP is used in the design of the LNA due to its low noise figure and high impedance input. As for the RFA design,FET EPA018A was used. The LNA and the RFA used T lumped reactive element network and microstrip line matching network. Two 3 dBπ -attenuators were inserted at the input and output of the RFA to isolate the system from the reflected load power. A Wilkinson power divider is developed for two equal power structures using impedance microstrip line technique. Microstrip technology was used for designing the Chebyshev filter. The result of each module for the front end is presented.